Small round cell sarcomas - Cidre-Aranaz, Florencia; Watson, Sarah; Amatruda, James F.; Nakamura, Takuro; Delattre, Olivier; de Alava, Enrique; Dirksen, Uta; Grünewald, Thomas G. P. (Nature reviews. Disease Primers, 2022)
Undifferentiated small round cell sarcomas (SRCSs) of bone and soft tissue comprise a heterogeneous group of highly aggressive tumours associated with a poor prognosis, especially in metastatic disease. SRCS entities mainly occur in the third decade of life and can exhibit striking disparities regarding preferentially affected sex and tumour localization. SRCSs comprise new entities defined by specific genetic abnormalities, namely EWSR1-non-ETS fusions, CIC-rearrangements or BCOR genetic alterations, as well as EWSR1-ETS fusions in the prototypic SRCS Ewing sarcoma. These gene fusions mainly encode aberrant oncogenic transcription factors that massively rewire the transcriptome and epigenome of the as yet unknown cell or cells of origin. Additional mutations or copy number variants are rare at diagnosis and, depending on the tumour entity, may involve TP53, CDKN2A and others. Histologically, these lesions consist of small round cells expressing variable levels of CD99 and specific marker proteins, including cyclin B3, ETV4, WT1, NKX3-1 and aggrecan, depending on the entity. Besides locoregional treatment that should follow standard protocols for sarcoma management, (neo)adjuvant treatment is as yet ill-defined but generally follows that of Ewing sarcoma and is associated with adverse effects that might compromise quality of life. Emerging studies on the molecular mechanisms of SRCSs and the development of genetically engineered animal models hold promise for improvements in early detection, disease monitoring, treatment-related toxicity, overall survival and quality of life.
Gesehen am 25.01.2023